AN ANALYSIS ON THE SECONDARY SCHOOL STUDENTS BURNOUT IN TERMS OF ACADEMIC SELF-EFFICACY, PARENTAL MONITORING, SOCIAL SUPPORT AND LEISURE TIME ACTIVITIES - Meral SERT AĞIR (International Journal of Eurasia Social Sciences, 2018)
Students at the stages of education, where the pressure of academic performance is felt more intensely, face the problem of burnout like adults in the business world. This situation affecting the attitudes of students towards education environments and education negatively is conceptualized as school burnout. Studies emphasize that school burnout is more intense in secondary and high school education where choices related to the future and expectations become significant in addition to the developmental problems. This study was carried out based on the opinion that expectations and anxiety about the importance of preparation and high performance can cause school burnout in students from the 6th grade to the end of the 8th grade. In this context, the aim of the study is to examine secondary school student burnout in terms of academic self-efficacy, parental monitoring instrument, social support and leisure activities. 396 students from the 6th, 7th, and 8th grade of secondary school in İstanbul province, Kadıköy district participated in this study. The study was designed in a descriptive research model and the data were analyzed in the SPSS program by using t test, variance and correlation analysis techniques. The data of the study was obtained using School Burnout Scale, Academic Self-Efficacy Scale, Parental Monitoring Scale, Child and Adolescent Social Support Scale and personal information form. As a result of the study, a significant relationship was found between significant differentiation and related properties at the level of (p<0.05) according to gender, age, grade, academic achievement, family characteristics and leisure activities.